The Middle Distance: A Reflection on Craft and Art - Cheng, University of Newcastle, Australia, Boey Kim (Asiatic: IIUM Journal of English Language and Literature, 2012)
In The Breaking of Style Helen Vendler examines the point in three poets’ careers when a radical departure from an established style occurs, often in response to a crisis or a change in orientation to art and life. For me the moment of rupture or reversal occurred with the act of migration. From movement and departure, my work has gravitated to a poetic of return and homecoming. The essay attempts to identify this moment of change, and also traces the threads of continuity, the abiding influences from my beginnings as a writer, and which are continuing to shape my emigrant life and work.